Immunoassays Based on Hot Electron-Induced Electrochemiluminescence at Disposable Cell Chips with Printed Electrodes - Grönroos P; Nur-E-Habiba; Salminen K; Nissinen M; Tuomaala T; Miikki K; Zhang Q; Wei N; Kauppinen E; Eskola J; Härmä H; Kulmala S (MDPI, 2022)
Novel hot electron-emitting working electrodes and conventional counter electrodes were created by screen printing. Thus, low-cost disposable electrode chips for bioaffinity assays were produced to replace our older expensive electrode chips manufactured by manufacturing techniques of electronics from silicon or on glass chips. The present chips were created by printing as follows: (i) silver lines provided the electronic contacts, counter electrode and the bottom of the working electrode and counter electrode, (ii) the composite layer was printed on appropriate parts of the silver layer, and (iii) finally a hydrophobic ring was added to produce the electrochemical cell boundaries. The applicability of these electrode chips in bioaffinity assays was demonstrated by an immunoassay of human C-reactive protein (i) using Tb(III) chelate label displaying long-lived hot electron-induced electrochemiluminescence (HECL) and (ii) now for the first time fluorescein isothiocyanate (FITC) was utilized as an a low-cost organic label displaying a short-lived HECL in a real-world bioaffinity assay.